Cost of nursing care for patients with venous vascular ulcer - Ambrosio-Ramírez, Cristian Camilo; Medina-Garzón, Mauricio (Universidad y Salud, 2023)
Introduction: The venous vascular ulcers care has become a public health problem due to its high incidence and the social and economic impact it causes. Objective: To determine the direct costs of nursing care of people with venous vascular ulcers treated at a health service provider facility in Bogota, Colombia. Materials and methods: Observational, descriptive, retrospective study carried out between January 1, 2019 and January 31, 2020, which focused on the review of medical records of patients with venous vascular ulcer. The sample included 52 medical records that were selected through a nursing assessment instrument. The variables of age and gender were analyzed through descriptive statistics and cost analysis. Results: Female was the predominant gender (69.24%) and the average age was 64 years. The direct cost was 70.109.504.76 COP, whereas the average estimate was 1.348.259 COP, which included the cost of dressings, elastocompression, cleaning, and consultation. Conclusion: The costs of venous vascular ulcers care are included in the care packages, which include costs of healing and consultation. Nevertheless, they are not explicit for nursing.